AN EVALUATION OF WH-QUESTION IN ENGLISH IN MIND TEXTBOOK AN BRIGHT AN ENGLISH TEXTBOOK SEEN IN TERMS OF BLOOM’S NEW TAXONOMY - Intan Kristen G. Takasana (Universitas Negeri Manado, 2020)
The study aimed at identifying and analyzing the types and levels of WH-question in two English Textbooks namely, English in Mind Textbook (EIM) and Bright An English Textbook (BAE) for eighth grade junior high school. The objective of the analysis was to evaluate the WH –questions in the light of the Bloom’s New Taxonomy (1956) Taxonomy learning objectives ( Remembering, Understanding, Applying, Analyzing, Evaluating, Creating).Content analysis was used to conducted all the WH-questions in the two textbooks. All the WH-questions were collected, listed, and analyzed according to Bloom’s New Taxonomy. The result from a total of 140 questions (70 questions in EIM and 70 questions in BAE) showed that most of the questions were align with remembering , understanding, and applying as the three lower – level categories, while analyzing, evaluating, and creating as the three higher-level categories constitude the lowest frequency in the two textbooks.Another result also for the proportion of higher-order questions in both Textbook showed that EIM received higher distribution while BAE constitute the highest distribution on lower-order questions. The result indicate that the textbooks failed to engage learners in the questions requiring higher levels of cognitive learning objectives.In the light of the results, the researcher suggested to modified the questions in the textbooks to cover the six levels of Bloom’s new Taxonomy and to train teachers and author of textbook to use and write question following the Bloom’s new Taxonomy